The CARE project – study protocol and pilot results from the Polish population - Krupa, Anna Julia; Galderisi, Silvana; Mucci, Armida; Gondek, Tomasz; Lengvenyte, Aiste; Dudek, Dominika; Siwek, Marcin (Frontiers in Psychiatry, 2025)
IntroductionNegative symptoms of schizophrenia (SZ) are a critical unmet need of SZ treatment. In the past years, clinical tools were developed and guidance papers for the evaluation and management of negative symptoms of SZ were published. The CARE (Competence and confidence Assessment of early career psychiatrists’ (ECPs) ability to evaluate and manage negative symptoms of SZ) project was designed to examine the competence and confidence of ECPs in assessing and treating negative symptoms of SZ.ObjectiveTo publish the protocol of the CARE project and a pilot analysis of the data obtained from the Polish sample.MethodsThe CARE project is an international cross-sectional 23-item online survey on competence and confidence in assessing and treating negative symptoms of the ECPs from European countries. This work includes the protocol of the CARE project and a pilot analysis of 140 responses from the Polish ECPs population.ResultsThe majority of the participants were trainees (67.2%), not engaged in clinical research (69.3%), reported placement in clinics/wards specialized in SZ care (77.1%) and inclusion of theoretical courses (54.3%) in their specialist training curriculum, and participation in extra-curricular training (62.9%) on the negative symptoms. Few ECPs (6.4%) correctly identified the negative symptoms domains, although the majority of them (55%) reported feeling well-trained to administer and interpret at least one tool for the assessment of the negative symptoms. Respectively, 32.8% and 25.9% reported feeling competent in evaluating and managing the negative symptoms. Specialist status and longer experience were linked to higher likelihood of feeling competent in assessment and management of the negative symptoms. The large majority of ECPs (87.1%) agreed that there should be more emphasis on the negative symptoms of SZ in specialist training. Engagement in clinical research was linked to higher likelihood of correctly identifying the domains of negative symptoms.ConclusionThe results from the Polish ECPs population indicate a very limited knowledge and preparedness to evaluate and manage negative symptoms of SZ. The CARE study will explore the European ECPs’ gap in knowledge and skills in the evaluation and management of the negative symptoms of SZ to inform future educational actions.